Applications of declarative programming and knowledge management 18th International Conference, INAP 2009, Évora, Portugal, November 3-5, 2009, Revised Selected Papers - Abreu, Salvador; Seipel, Dietmar (Springer Berlin Heidelberg, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the 18th International Conference on Applications of Declarative Programming and Knowledge Management, INAP 2009, held in Évora, Portugal, in November 2009. The 12 revised full papers presented together with 2 invited talks were carefully reviewed and selected during two rounds of reviewing and improvement. The conference comprehensively covers the impact of programmable logic solvers in the internet society, its underlying technologies, and leading edge applications in industry, commerce, government, and societal services. The topics of the selected papers concentrate on three currently important fields: foundations and extensions of logic programming, databases and query languages, declarative programming with logic languages, and applications thereof